Identification and characterization of three Vibrio alginolyticus non-coding RNAs involved in adhesion, chemotaxis, and motility processes - Huang, Lixing; Hu, Jiao; Su, Yongquan; Qin, Yingxue; Kong, Wendi; Ma, Ying; Xu, Xiaojin; Lin, Mao; Yan, Qingpi (Frontiers in Cellular and Infection Microbiology, 2015)
Adhesion capability to fish mucus is considered to be a key virulence factor of Vibrio alginolyticus, while the molecular mechanism is still unclear. Non-coding RNAs (ncRNAs) play a crucial role in the intricate regulation of bacterial gene expression, affecting the pathogenicity of bacteria. With high through-put sequencing and bioinformatics analysis, we identified three ncRNAs predicted to regulate the bacterial chemotaxis pathway in our previous study, which might play a key role in the adhesion process of V. alginolyticus. In the present study, we validated the effects of these three ncRNAs on their predicted target genes and the role of these three ncRNAs in the adhesion process of V. alginolyticus with RNAi, QPCR, capillary assay, and in vitro adhesion assay. According to our results, the expression of these ncRNAs and their predicted target genes were confirmed by QPCR, which reinforced the reliability of the sequencing data and the target prediction. We found that over-expression of these ncRNAs were capable of reducing the chemotactic and adhesion ability of V. alginolyticus, while the expression levels of their target genes were significantly reduced. Our results indicated that: 1) these three ncRNAs were really able to regulate the bacterial chemotaxis pathway; 2) these three ncRNAs played a key role in the adhesion process of V. alginolyticus.